Il Novecentismo - Farinelli, Patrizia (Vestnik za tuje jezike, 2014)
This article, with reference to theoretical and polemical essays collected in L'Avventura novecentista (1938), retraces Bontempelli's perspective on the project of cultural renewal (the Novecentism), which he himself promoted in the 1920's. This article presents not only the battles he sustained and his farsightedness, but also the problems or rather the challenges of this project. Along these challenges came the utopian battle against relativism, the tendency to defend the autonomy of art and the contemporary requirement that this autonomy be open to the necessities of that time, as well the attempt to conciliate an artistic work, inclined to break the norms and expectations, with a concept of popular literature and art.
Keywords: Bontempelli, Massimo, 1878-1960; italijanska književnost; novecentizem; magični realizem; kulturna prenova; avtonomija umetnosti